Does Giving to Charity Lead to Better Health? Evidence from Tax Subsidies for Charitable Giving - Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2014)
In the United States, charitable contributions can be deducted from taxable income making the price of giving inversely related to the marginal tax rate. The existing literature documents that charitable giving is very responsive to tax subsidies, but often ignores the spillover effects of such policies. On the other hand, a growing body of literature documents that giving to others reduces stress and strengthens the immune system, which results in better health and longer life expectancy. These findings imply that tax subsidies for charitable giving may have positive spillover effects on health. This paper investigates this hypothesis using data from Center on Philanthropy Panel Study (COPPS), the philanthropy module of the Panel Study Income Dynamics (PSID). Understanding the spillover effects of charitable subsidies on health is quite important given the existing literature that links health status to several important economic outcomes. The results show that charitable subsidies have positive spillover effects on health. In particular, the implied cross-price elasticity of health index with respect to giving is -0.13. These results are robust to potential endogeneity of income and highlight the positive externalities created by tax subsidies for charitable giving.
Keywords: H24; H31; I10; 330; charitable giving; health status; tax subsidies